DEVELOPMENT OF INTEGRATED NATURAL SCIENCE E-POCKET BOOK CONTAIN SCIENTIFIC LITERACY ON THE MATERIAL HUMAN RESPIRATORY SYSTEM FOR STUDENT OF SMP/MTs - Afifah Putri; Tuti Lestari (Universe, 2021)
This research is based on the weakness of the scientific literacy of Indonesian students and limitations of the teaching materials provided by schools in learning natural science. The effort that can be done is honorate the ability of scientific literacy of students and develop supplement teaching materials that can help students memorize the learning and improve the ability of scientific literacy. The aim of this research to develop a learning supplement in shape electronic pocket book (e-pocket book) of intergrated natural science contain scientific literacy on the material human respiratory system for student of SMP/MTs. The type of research conducted is research and development by using ADDIE model which is done only until the development stage due to the limitations of the researchers. The result of validity was 90,96% with chategori very valid, practicality by teachers was very practiced with value 98,37%, and by the students was very practiced with value 92,59%. This research shows that the e-pocket book was classified as valid and practical.